Studies of liver insulin receptors in non-obese and obese human subjects. - Arner, P (1983)
The insulin-binding isotherms and the structural composition of human liver insulin receptors were examined by using plasma membranes that were prepared from liver biopsies of nine non-obese and 10 obese subjects undergoing elective surgery. The insulin-binding characteristics of liver membranes from non-obese subjects were quite similar to those previously described in rat liver membranes. However, when the membranes from obese subjects were compared with the non-obese group, insulin-binding activity was reduced by 50% (P less than 0.01). The reduction in obesity resulted primarily from a decrease in total receptor number, although a small decrease in receptor affinity was also observed. Insulin binding was not correlated with sex or with the fasting plasma insulin level. The insulin-binding sites of liver membranes were affinity-labeled with 125I-insulin and the cross-linking reagent, disuccinimidyl suberate. The liver membranes from both the non-obese and the obese group had heterogenous (nonreduced) insulin-binding species of 300,000, 260,000, and 150,000 mol wt, which were again comparable to the findings reported in rat liver. Sulfhydryl reduction demonstrated a major sub-unit of 125,000 and a minor component of 40,000-45,000 in both groups. These results indicate a close similarity between the hepatic insulin receptor of man and the more intensely studied rat hepatic receptor. Obesity in human subjects is associated with a loss of hepatic insulin receptors. This alteration may contribute to the insulin resistance reported in this organ as well as to obesity-mediated glucose tolerance.